Clinical photography in dermatology using smartphones: An overview - K T Ashique; Feroze Kaliyadan; Sanjeev J Aurangabadkar (Wolters Kluwer Medknow Publications, 2015)
The smartphone is one of the biggest revolutions in the era of information technology. Its built in camera offers several advantages. Dermatologists, who handle a specialty that is inherently visual, are most benefited by this handy technology. Here in this article, we attempt to provide an overview of smartphone photography in clinical dermatology in order to help the dermatologist to get the best out of the available camera for clinical imaging and storage